Des jardiniers à l’épreuve du sol urbain - Marie Grenet; Élisabeth Rémy; Marine Canavèse; Nathalie Berthier (Projets de Paysage)
Community gardens are often created in abandoned urban sites. These areas are often marked by different potential sources of soil contamination. This raises the issue of the re-use of these sites. It is necessary to address the issue of how soil contamination is managed, experienced and perceived by gardeners : which forms of contamination affect them most ? How can the soil and its quality be appreciated in town ? A study of the users’ statements, actions and expertise will make it possible to understand how gardeners address the question of soil contamination. The objective is to present the different points of view concerning soil contamination observed during our field studies and which lead to political discourses concerning the quality of urban environment.